Evaluation of Relationship between Academic Motivation and Achievement in Students of Zanjan University of Medical Sciences - Atefeh Yousefi; Aalie Jamshid nejad; Nima Moatamed (Journal of Medical Education Development, 2018)
Background & Objective: Considering the significant importance of academic achievement of medical students in the improvement of society health, this study aimed to evaluate academic motivation and its relationship with academic achievement. Materials and Methods: This cross-sectional research was conducted on junior students in fields of medicine, dentistry and pharmacy of Zanjan University of Medical Sciences, Zanjan, Iran in 2016. Subjects were selected through convenience sampling and filled Herman’s motivation questionnaire. Data analysis was performed in SPSS using Pearson’s correlation coefficient and t-test (P<0.05). Results: In this research, 85% of the students were within the age range of 24-26. In total, 53.1% of students were male and 46.9% of them were female. In terms of marital status, 85% and 15% of the participants were single and married, respectively. Moreover, 74.1% of the students had a quota and 25.9% had no quota. Furthermore, 52.4% were living in dormitories and 47.6% were residing in other places. After the evaluation of the medicine, pharmacy, and dentistry students, their academic motivation score was 2.83, 2.87, and 2.86, respectively. According to the results, students residing in places other than dormitories had a higher motivation level, compared to those living in dormitories. Moreover, a significant relationship was observed between motivation and score of basic science GPA. Conclusion: Given the fact that only living in dormitories reduced motivation in students, it is recommended that counseling meetings be held to familiarize students with this type of life and facilities in dormitories be improved to increase the motivation of students residing in dormitories.